2018
DOI: 10.1039/c8cp05774e
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation and growth of gold nanoparticles initiated by nanosecond and femtosecond laser irradiation of aqueous [AuCl4]

Abstract: Irradiation of aqueous [AuCl4]− with 532 nm nanosecond (ns) laser pulses produces monodisperse (PDI = 0.04) 5-nm Au nanoparticles (AuNPs) without any additives or capping agents via a plasmon-enhanced photothermal autocatalytic mechanism. Compared with 800 nm femtosecond (fs) laser pulses, the AuNP growth kinetics under ns laser irradiation follow the same autocatalytic rate law, but with a significantly lower sensitivity to laser pulse energy. The results are explained using a simple model for simulating heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(83 citation statements)
references
References 86 publications
5
76
0
Order By: Relevance
“…Like PLAL, laser photochemical reduction can produce sub-5 nm Au NPs at room temperature in aqueous solution without added surfactants or stabilizers [30,31]. Laser photochemical reduction is typically performed using laser pulses of picosecond [27][28][29][30] or femtosecond [31][32][33][34][36][37][38][39][40][41][42][43] duration, although optical breakdown of water during micrometer-scale nanosecond UV laser irradiation has been identified [44], and Au NP synthesis with ns pulses at 532 nm was recently reported [43]. Femtosecond laser pulses form plasma primarily through photoionization instead of cascade ionization, which enables precise control over the plasma electron density by varying the laser peak intensity [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like PLAL, laser photochemical reduction can produce sub-5 nm Au NPs at room temperature in aqueous solution without added surfactants or stabilizers [30,31]. Laser photochemical reduction is typically performed using laser pulses of picosecond [27][28][29][30] or femtosecond [31][32][33][34][36][37][38][39][40][41][42][43] duration, although optical breakdown of water during micrometer-scale nanosecond UV laser irradiation has been identified [44], and Au NP synthesis with ns pulses at 532 nm was recently reported [43]. Femtosecond laser pulses form plasma primarily through photoionization instead of cascade ionization, which enables precise control over the plasma electron density by varying the laser peak intensity [26].…”
Section: Introductionmentioning
confidence: 99%
“…Femtosecond laser pulses form plasma primarily through photoionization instead of cascade ionization, which enables precise control over the plasma electron density by varying the laser peak intensity [26]. This ability to control reactive species formation rates with the peak intensity enables substantial control over Au NP size distributions [29,31,35,43].…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of GO, we recently reported that photoreduction of [AuCl 4 ] À with 532 nm, 8 ns or 800 nm, 30 fs pulses in water under otherwise similar conditions (average laser power, beam diameter) produce different Au NP size distributions. 47 These results are attributed to the distinct reduction mechanisms induced by the two lasers. Photoreduction with fs lasers is driven by reactive species such as hydrated electrons formed by water photolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Photoreduction with fs lasers is driven by reactive species such as hydrated electrons formed by water photolysis. [47][48][49][50] In contrast, ns laser pulses induce thermal decomposition of the [AuCl 4 ] À precursor and photothermal autocatalytic reduction in the presence of AuNPs due to the 532 nm laser wavelength being resonant with the surface plasmon resonance of Au. 47 In this work, we report on the role of GO in determining Au NP size distributions, prGO chemical composition, and catalytic activity of Au-prGO nanocomposites produced using ns and fs lasers.…”
Section: Introductionmentioning
confidence: 99%
“…The structure and shape of the nanoparticles is essential for their chemical and magnetic behavior and much effort has been put into techniques to control these properties, both during synthesis and after [11]. As an examples of postsynthesis modification of nanoparticle properties utilizing laser illumination of nanoparticle solutions, illumination with intense nanosecond laser pulses exciting plasmon modes at 532 nm has been shown to give rise to highly monodisperse nanoparticles in the case of Au [12]. For characterizing these processes in more detail, the structural dynamics during pulsed laser heating, melting and resolidification of Au nanoparticles have been measured with time-resolved x-ray scattering experiments [13][14][15], but the direct structural dynamics of a solid-solid phase transition has to our knowledge not been reported.…”
Section: Introductionmentioning
confidence: 99%